Productivity and Cost Analysis of Forest Harvesting Operation in Matang Mangrove Forest, Perak, Malaysia - Tindit, Albert Empawi; Gandaseca, Seca; Nyangon, Laurna; Pazi, Ahmad Mustapha Mohamad (Forestry Faculty, Universitas Hasanuddin, 2017)
Matang Mangrove Forest is under systematic management since 1902 and still considered as the best managed mangrove forest in the world. This research was conducted to measure the time and productivity of forest harvesting operation and also to analyze the cost and revenue of mangrove forest harvesting operation at Matang mangrove forest. This project had been carried out in cooperation with Seri Sepetang Enterprise, one of the harvesting licenses in Kuala Sepetang, Perak. Data collections were taken in every station starting from standing tree until to the Kiln-Drying jetty. The data then calculated by using the formulas of productivity and cost analysis. As the result, the productivity for felling, bucking and debarking, the manual skidding using wheel-barrow and the water transportation are 1.84 tan/hour, 3.82 tan/hour and 4.64 tan/hour respectively. The cost for each operation of 9 tan log volume for felling, bucking and debarking, the manual skidding using wheel-barrow and the water transportation are RM 56.88, RM 10.80 and RM 36.72 respectively. As the revenue, the company paid RM 260 per 9 tan of log for the in-forest operation (felling, manual skidding and loading to the ship) and pay RM 80 per 9 tan for the water transportation, and they gained the net profit of RM 192.32 and RM 43.28 respectively. The average of forest harvesting operation is twice operation in a day (equal with 2 x 9-ton volume of log production a day), so they will gain a double profit. In conclusion, the forest harvesting operation is sustainably managed for supplying the raw material of charcoal industries in Matang mangrove forest. Since, they work manually and spend much energy in this forest harvesting operation, so for further study it recommends to conduct the ergonomics evaluation during forest harvesting operation at Matang Mangrove Forest.